A diversidade nas organizações brasileiras: estudo sobre orientação sexual e ambiente de trabalho - Irigaray, Hélio Arthur (2008)
The object of this research is to understand the impact of the multiple sexual orientations on the organizations and how this diversity is perceived by the homo, bi and heterosexual employees. Ontologically, this study uses the critical postmodernism, specifically the Queer Theory, which deconstructs all conventional categories of sexuality and gender. The field research consisted of four visits to 13 large companies, in Rio de Janeiro and São Paulo, between July 2005 and November 2007, as well as 95 interviews, divided in four groups. The first one was composed of heterosexual and the second of homo and bisexual individuals, who were informed of the real object of this research. As a discrepancy of what the heterosexuals said during the interviews and their attitudes in the work environment as well as their comments to other heterosexuals was observed, a control-research was also carried out. Two othe groups – one of heterosexuals and the other of homo and bisexuals – were interviewed; nevertheless, they were informed that the object of the research was to study health in the workplace. The fieldnotes as well as the interviews were transcripted and submitted to discourse and conversational analyses. The findings were presented in five sections: the individual dimension, the social dimension, the workplace environment itself, the psychosomatic costs and, finally, the outcome of the research on health at the workplace. This study revealed that, when questioned about discrimination at the workplace, gays, lesbians and bisexuals tend to recognize the existence of such practices, as well as advocate that they also have been a victim of such. On the other hands, the heterosexuals tend to minimize the existence of such practices, as well as deliver a politically-correct speech. Notwithstanding, it was clear that the heterosexuals have introjected the masculine hegemonic paradigm, which was been built historically through social practices and, discriminatory attitudes and comments are disguised by the Brazilian sense of humour and informality. On the other hand, the research that was guided by the investigative question on health at the workplace revealed that, as the were not being confronted directly, the heterosexuals felt more at ease to express themselves, using homophobic expressions and referring to discriminatory practices. Yet, the homo and bisexuals attained to the question of health itself and, rarely, did they refer or mention discriminatory practices in the workplace. At the bottom line this study confirmed that the sexual orientation per se is only a component of an individual’s personality and, although it may be the ground for prejudice and discrimination, these practices are also caused due other factors such as gender, race, and social status.